After legal equality : family, sex, kinship - Leckey, Robert (Abingdon, Oxon : Routledge, 2015)
'Groups seeking legal equality often take a victory as the end of the line. Once judgment is granted or a law is passed, coalitions disband and life goes on in a new state of equality. Policy makers too may assume that a troublesome file is now closed. This collection arises from the urgent sense that law reforms driven by equality call for fresh lines of inquiry. In unintended ways, reforms may harm their intended beneficiaries. They may also worsen the disadvantage of other groups. Committed to tackling these important issues beyond the boundaries that often confine legal scholarship, this book pursues an interdisciplinary consideration of efforts to advance equality, as it explores the developments, challenges, and consequences that arise from law reforms aiming to deliver equality in the areas of sexuality, kinship, and family relations. With an international array of contributors, After Legal Equality: Family, Sex, Kinship will be an invaluable resource for those with interests in this area.' --
'This timely interdisciplinary and international collection studies the aftermath of legal reforms made in the name of equality - including 2013's same-sex marriage for England and Wales and the striking down of America's Defense of Marriage Act - and provides methodological, conceptual and theoretical resources for further research. Inspired by queer theory and feminist theory, the chapters' methodologies range from discourse analysis to empirical research. Chapters focus on the UK, Canada, and the US, examining legal developments around same-sex couples and parenting, fathers' rights and equal parenting, cohabitation and care, and organizing for racial equality. This contextual, socio-legal work will be a valuable resource for undergraduate and graduate students and researchers in law, sexuality and gender studies, sociology, and political science in the UK, the USA, and Canada as well as in South Africa, Australia and New Zealand'--
Making family law less sexy ... and more careful / Jonathan Herring -- Equality : an uncomfortable fit in parenting law / Susan B. Boyd -- Men, gender and fathers' rights'after legal equality' : new formations of rights and responsibilities in family justice / Richard Collier -- Economic justice after legal equality : the case for caring queerly / Janet R. Jakobsen -- Cameos from the margins of conjugality / Kim Brooks -- Leaping without looking / Helen Reece -- Taxing times for lesbians and gay men : twenty years later / Claire F.L. Young -- The historiographical operations of gay rights / Roderick A. Ferguson -- Tackling inequality in the intimate sphere : problematizing love and violence in same-sex relationships / Catherine Donovan -- (Re)inscribing the heteronormative family : same-sex relationships and parenting'after equality' / Rosie Harding -- Sexuality and children post-equality / Daniel Monk.
'A GlassHouse Book.'
Includes bibliographical references and index.
Keywords: Same-sex marriage -- Law and legislation; Gay couples -- Legal status, laws, etc; Equality before the law; Homosexuality -- Law and legislation; Gay rights; Queer theory